Photo Relief Map of North America - Brion, Henry F.; McClure, Edmond (Society for Promoting Christian Knowledge (Great Britain), 1885)
This photo relief map shows North and Central America and the surrounding areas. Blue outlining marks countries, roads, and bodies of water. States, territories, and provinces throughout the continent are marked in dotted lines and labeled. Geographic features are marked with relief shown by spot heights and shading. A note in the lower left corner says, "Heights are given in Feet above Sea Level."